IMPROVING FARMER PARTICIPATION IN DIGITAL PLATFORM BY USING GAMIFICATION: AN AGENT- BASED MODEL APPROACH - FRANCISKA FAJARINI, PUTU
Digital agriculture emerges as a new method for effectively managing coordination in agriculture. It improves the agricultural system by reinforcing agriculture coordination through adequate knowledge sharing as an outcome of data and information sharing. Unfortunately, the adoption rate of digital agricultural technology by smallholder farmers in Indonesia remains low. Personality dimensions and low motivation of farmers are reasons for this low adoption rate. With these considerations in mind, it is essential to determine the right policies to increase adoption, especially of digital platforms among farmers in Indonesia. Like those mentioned earlier, the author used the motivational characteristics represented in the goal achievement theory as the underlying theory to determine the pattern of technology adoption among farmers. Achievement goals perceive as (moderately) particular competence standards and cognitive portrayals that focus on competencebased